METODE THINK PAIR SHARE UNTUK MENINGKATKAN KEMAMPUAN MENGINGAT DALAM PELAJARAN BIOLOGI DI SEKOLAH LENTERA HARAPAN GUNUNG AGUNG LAMPUNG - Febriyanti Siringo Ringo; Jessica Elfani Bermuli Elfani Bermuli (Jurnal Ilmiah Didaktika, 2020)
Understanding concepts is very important in learning. Remembering level is the first step of primary skill to be mastered that will enable students to understand a concept. The reality that the researcher found in grade IX Sekolah Lentera Harapan (SLH) Gunung Agung Lampung is not relevant to the concept. The students there have not reached the optimal remembering stage. Therefore, this research aims to find out the Think Pair Share (TPS) method is able to increase the students' remembering cognitive ability and to apply the TPS method to increase the students' remembering cognitive ability. The research method used is Pelton's Classroom Research model. The instruments used in data collection are tests, lesson plans, mentor's feedback, and journal reflection. The result reached were as follows: in the application of action 47%, in repetition I 63%, and in repetition II 95%. The systematic steps of application for the TPS method were: 1) thinking, 2) pairing, and 3) sharing. Research findings showed that the application of the TPS method is able to increase the students' remembering cognitive ability.